Comparative study of the Frankel (FR-2) and bionator appliances in the treatment of Class II malocclusion - de Almeida, M. R.; Henriques, JFC; Ursi, W. (Mosby, Inc, 2002)
The purpose of this investigation was to compare the dentoalveolar and skeletal cephalometric changes produced by the Frankel (FR-2) and bionator appliances in persons with Class 11 malocclusion. Lateral cephalograms were available for 66 patients of both sexes, who were divided into 3 groups of 22. The control group included untreated Class 11 children, with an initial mean age of 8 years 7 months; they were followed without treatment for 13 months. The FR-2 appliance group had an initial mean age of 9 years; those children were treated for a mean period of 17 months. The bionator group initially had a mean age of 10 years 8 months; on average, they were treated for 16 months. The results demonstrated no significant changes in maxillary growth during the evaluation period. Both appliances showed statistically significant increases in mandibular growth and mandibular protrusion, with greater increases in patients treated in the bionator group. Both experimental groups showed an improvement in the maxillomandibular relationship. There were no significant changes in growth direction, while the bionator group had a greater increase in posterior facial height. Both appliances produced similar labial tipping and protrusion of the lower incisors, lingual inclination, retrusion of the upper incisors, and a significant increase in mandibular posterior dentoalveolar height. The major treatment effects of bionator and FR-2 appliances were dentoalveolar, with a smaller, but significant, skeletal effect.